THE USE OF MICROWAVE FIELDS IN THE FOAMING PROCESS OF FLAT GLASS WASTE (International Journal of Engineering Sciences & Management Research, 2018)
The paper presents experimental results obtained in the manufacture process of glass foam from clear flat glass waste and coal ash, using silicon carbide as foaming agent. The heating of the powder mixture was achieved in microwave field, unlike other experiments of this type presented in literature. The physical features of the glass foams obtained by unconventional heating are similar to those made by conventional methods, having the advantage of a superior macrostructural homogeneity, which ensures them a better mechanical strength.